Metformin, the Rise of a New Medical Therapy for Endometriosis? A Systematic Review of the Literature - Stochino-Loi, Emanuela; Major, Attila L.; Gillon, Tessa E. R.; Ayoubi, Jean-Marc; Feki, Anis; Bouquet de Joliniere, Jean (Frontiers in Medicine, 2021)
Medical treatments for endometriosis aim to control pain symptoms and stop progression of endometriotic lesions. However, their adverse effects and their contraceptive effect in women who desire pregnancy, limit their long term use. Although there is only one clinical study investigating the effects of Metformin in women with endometriosis, Metformin seems to have in in vivo and in vitro studies an unique therapeutic potential. It may be helpful as an anti-inflammatory and antiproliferative agent in the treatment of endometriosis. As such Metformin may be more beneficial compared to other treatments, thanks to the lack of serious side effects.